Electronic anti‐injection effect for carbonyl in anchor group based on diphenylacetylene D2‐π‐A sensitizer in dye‐sensitized solar cells. (10th September 2020) - Chen, Shaorui; Pang, Zhihan; Wu, Wenjun
Summary: Up to now, in developing organic molecules for dye‐sensitized solar cells, the determining role of acceptors has not yet received enough attention. Herein, three novel sensitizers were prepared with D2 ‐π‐A structure, following cyanoacetic acid, acetic acid, and rhodanine‐3‐acetic acid as the acceptors, respectively. It was found that the thiocarbonyl and carbonyl groups, which are separated by two atoms with carboxyl group, effectively promoted molecular light harvesting, intramolecular charge transfer, and improved energy level matching, but a significant electron‐blocking effect occurred, which limited the enhancement of photoelectric conversion performance with rhodanine‐3‐acetic acid. From PT‐1 to PT‐3, the power conversion efficiency decreased sharply from 5.27% to 2.70%. As a result, an electronic anti‐injection effect of electron‐drawing unit in the anchor group compared with cyanoacetic acid was found for the development of organic sensitizer design. Abstract : Design and synthesis of novel D2 ‐π‐A structure sensitizers based on diphenylacetylene Improving light harvesting with rhodanine‐3‐acetic acid Electronic anti‐injection affected the photoelectric conversion efficiency.